THE IMMORALITY OF PRAYER. Issue 40 (9th April 2015) - Lyon, Ardon
Abstract : It's no surprise that one shouldn't pray for bad things to happen, for it's always wicked to attempt to bring about evil. But perhaps surprisingly one shouldn't pray for good things either. For if there is an Omnipotent, Omniscient and Omni-Benevolent Deity who intervenes at all in the workings of the world, then He will do whatever is best anyway, and if you pray for what He wouldn't otherwise have done then it must, perhaps unknown to you, be wrong. If there is no God then He will not answer your prayers, although they might be efficacious in other ways.